Language and Deed : Rediscovering Politics through Heidegger's Encounter with German Idealism - Schalow, Frank (Elementa, 1998)
This book examines Heidegger's controversial relation to politics as it grows out of his understanding of his predecessors in German Idealism, most notably, Hegel. This way of developing a dialogue between Heidegger and Hegel on the issue of politics provides an important context for questioning the former's link with National Socialism. Yet the book does not simply condemn Heidegger for his Nazi involvement nor claim that his thinking is free from dangerous political implications. On the contrary, a second level of questioning asks whether Heidegger's philosophy can be appropriated in alternative contexts which permit the affirmation of democratic principles. Thus the book concludes by examining the import which Heidegger's thought has on cultivating such democratic motifs as freedom of speech and civil disobedience. The book is especially of interest to advanced undergraduates, graduate students, and scholars in the areas of German idealism, phenomenology, social and political philosophy, and the history of philosophy.